Assessment of the quality of patient-orientated Internet information on surgery for diverticular disease. - Yeung, T; Mortensen, N (2012)
BACKGROUND: The Internet is a vast resource available for patients to obtain health information. OBJECTIVE: This study examines the quality of Web sites that provide information on diverticular disease, treatment options, and surgery. DESIGN: Two search engines (Google and Yahoo) and the search terms "surgery and diverticular disease" and "surgery and diverticulitis" were used. The first 50 sites of each search were assessed. Sites that fulfilled the inclusion criteria were evaluated for content and scored by using the DISCERN instrument, which evaluates the quality of health information on treatment choices. RESULTS: Two hundred sites were examined, of which 60 (30%) provided patient-orientated information. 50 sites (25%) were duplicated, 7 (3.5%) were links, 10 (5%) were advertisements, 14 (7%) were resources for clinicians, 9 (4.5%) were message forums, 27 (13.5%) were articles, and 15 (7.5%) were dead links. Of the 60 Web sites that provided patient information, only 10 (16.7%) had been updated within the past 2 years. Seventeen (28.3%) sites were affiliated with hospitals and clinics, but another 17 (28.3%) sites were associated with private companies with commercial interests. Although most Web sites contained information on symptoms, complications, investigations, and treatment options of diverticular disease, 20 (33.3%) did not describe any of the risks of surgery, and 45 (75%) did not provide information on the timescale of recovery postoperatively. Eighteen sites did not provide balanced information on treatment options; of these, 7 were biased toward medical treatment and 6 focused on laparoscopic surgery. Overall, only 22 (36.7%) were identified as being "good" or "excellent" with the use of the DISCERN criteria. CONCLUSIONS: The quality of patient information on surgery for diverticular disease is highly variable, and Web sites that are sponsored by private companies may be biased in discussing treatment options. There is potential for the Internet to provide valuable information, and clinicians should guide patients to access high-quality Web sites.